2003
DOI: 10.1128/aac.47.11.3470-3477.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of RhoA-Derived Peptides against Respiratory Syncytial Virus Is Dependent on Formation of Peptide Dimers

Abstract: A synthetic peptide containing amino acids 77 to 95 of the intracellular GTPase RhoA has previously been shown to inhibit replication of respiratory syncytial virus (RSV) in cultured cells. We show that residues 80 to 90 of RhoA are sufficient for this activity and that the cysteine residue at position 83 is critical. Further studies with an optimal peptide sequence containing amino acids 80 to 94 of RhoA revealed that the antiviral potency of the peptide is dependent on the oxidation of cysteine 83. Size-excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Similar to this study, in silico analyses showed the potent antiviral effects of AMPs against Betacoronavirus [ 27 , 39 ]. According to our results, the AMPs are attractive candidates as alternative to conventional antiviral drugs to control SARS-CoV-2 infection, because they offer several potential advantages, including specific anti-CoV effects, high selectivity, and do not be associated with severe adverse effects according to in vitro and in vivo assays [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to this study, in silico analyses showed the potent antiviral effects of AMPs against Betacoronavirus [ 27 , 39 ]. According to our results, the AMPs are attractive candidates as alternative to conventional antiviral drugs to control SARS-CoV-2 infection, because they offer several potential advantages, including specific anti-CoV effects, high selectivity, and do not be associated with severe adverse effects according to in vitro and in vivo assays [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this, we have also observed that the addition of positively charged lysine residues to RhoA-derived peptides from the aa 77 to 95 region abolishes their antiviral activity. This observation was made when lysine residues were added to several previously tested peptide 77-95 derivatives (5) in an effort to simplify their elution from a reverse-phase high-performance liquid chromatography column. In each instance, the addition of three C-terminal lysines resulted in a loss of antiviral activity compared to the corresponding peptide without the C-terminal lysines (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Based on truncation studies, it was shown that a slightly shorter peptide comprising amino acids (aa) 80 to 94 of RhoA was optimal for anti-RSV activity. Interestingly, the antiviral activity of this peptide was dependent upon the oxidation of an internal cysteine residue, resulting in the formation of peptide dimers (5). This dependence on an increased molecular weight, coupled with the anionic nature of the optimal peptide sequence, suggested that the antiviral activities of RhoA-derived peptides are unrelated to a specific in vivo F-RhoA interaction, but rather are a reflection of their similarities to other antiviral polyanions.…”
mentioning
confidence: 96%
“…A similar pharmacological approach consisted of the peptide Rho‐A, which inhibits the syncytia formation that is characteristic of hRSV infection. RhoA is a small GTPase that is involved in the fusion process and the inhibitor of this protein has been tested in HEp‐2 cells and mice, with promising results …”
Section: Drug Design To Treat Rsv Infectionmentioning
confidence: 99%
“…RhoA is a small GTPase that is involved in the fusion process and the inhibitor of this protein has been tested in HEp-2 cells and mice, with promising results. 56,61 Besides peptides that inhibit hRSV fusion, there are several other chemical compounds that impair the fusion process. The benzimidazole JNJ2408068 has shown a high antiviral activity, 100 000 times higher than ribavirin and acts by preventing virus fusion and syncytia formation.…”
Section: Drug Design To Treat Rsv Infectionmentioning
confidence: 99%